Extraction And Purification Of Pithecellobium Dulce Bioactive Compounds By HPLC And Flash Chromatography (International Journal of Environmental Sciences, 2025)
Phytochemicals, being secondary metabolites made by plants, are well-known for their many uses in medicines and help a lot in finding and producing new drugs. Being widely known as jungle jalebi, Pithecellobium dulce (Pd) is a tropical fruit plant and is valued for its many medicinal properties. This work was focused on analyzing the phytochemical content of P. dulce fruit extract and improving the methods used to obtain its main bioactive components. Ethanol was used as a solvent in the Soxhlet extraction to get the crude plant extract. A preliminary screening of phytochemicals found that the plant contains alkaloids, flavonoids, phenols, tannins, terpenoids and saponins. HPLC confirmed the presence of gallic acid, known for its antioxidant and anti-inflammatory properties, after 2.8 minutes of analysis and showed a high degree of linearity when compared to the standard (R² = 0.993278, p < 0.05). The solution was then purified using flash chromatography to isolate gallic acid which appeared as well-separated peaks and was readily isolated according to its polarity and absorption profile at 280 nm. The results suggest that the purified gallic acid meets the required standards for pharmacological studies. The study suggests that P. dulce contains promising therapeutic compounds and using optimized methods like Soxhlet extraction, HPLC and flash chromatography plays an important role in separating and identifying them. The results point to the potential of P. dulce fruit in creating plant-based drugs and natural remedies, encouraging further study in laboratories as well as animal and human experiments.